X‐ray photoelectron spectroscopy study on the photodegradation of copolyester model compounds. Issue 2 (27th July 2020) - Arangdad, Kiarash; Yildirim, Erol; Detwiler, Andrew; Cleven, Curtis D.; Burk, Christopher; Shamey, Renzo; Pasquinelli, Melissa A.; Freeman, Harold; El‐Shafei, Ahmed
Abstract: The photodegradation of irradiated PETG and PCCT model compounds namely Tm‐CHDM‐Tm and Tm‐TMCD‐Tm, where Tm refers to the methyl ester of terephthalic acid, CHDM refers to 1, 4‐cyclohexanedimethanol, and TMCD refers to tetramethyl‐1, 3‐cyclobutanediol, was analyzed using X‐ray photoelectron spectroscopy. Photodegradation products were characterized based on high resolution O1s x‐ray photoelectron spectroscopy (XPS) spectra and the spectra of irradiated model compounds showed a decrease in the relative intensity of CO compared to the CO peak. The percentage of CO formation in irradiated model compounds changed in proportion to irradiation time and showed that the model compound containing CHDM was slightly more UV stable than the TMCD based model compound. Photodegradation mechanisms for model compounds were proposed based on XPS spectra. In parallel studies, density functional theory calculations were performed as an approach to predict degradation products, to help interpreting the XPS spectra of model compounds and characterize the reactivity of model compounds. Abstract :